2023
DOI: 10.3389/ffgc.2023.1192382
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production, carbon stock and sequestration potential of prominent agroforestry systems in north-western Himalaya, India

Ishrat Saleem,
J. A. Mugloo,
Nazir A. Pala
et al.

Abstract: Agroforestry is an age-old practise of integrating farming with practises, preferably on the same unit of land on sustainable basis. There is tremendous scope for Agroforestry because India has achieved self-sufficiency in food production. Now its attention is becoming more focused on the ecological problems and shortage of fuel, fodder and other outputs as well as unemployment. So, agroforestry land use systems offer a better option by serving as carbon sinks and contributing in attaining food safety, subsist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…[12], Saleem et al [13] evaluated different land use option for its C storage and sequestration in Northwestern Himalayas and concluded that after forestry land use, agroforestry could achieve the highest C content and sequestration. Niether et al [14] also corroborate that agroforestry for cocoa is capable of sequestering 2.5 times more C in the cocoa system as compared to monoculture and cultivation.…”
Section: Agroforestry For Global Sustainabilitymentioning
confidence: 99%
“…[12], Saleem et al [13] evaluated different land use option for its C storage and sequestration in Northwestern Himalayas and concluded that after forestry land use, agroforestry could achieve the highest C content and sequestration. Niether et al [14] also corroborate that agroforestry for cocoa is capable of sequestering 2.5 times more C in the cocoa system as compared to monoculture and cultivation.…”
Section: Agroforestry For Global Sustainabilitymentioning
confidence: 99%